2021
DOI: 10.1093/icesjms/fsab076
|View full text |Cite
|
Sign up to set email alerts
|

Status of Indian marine fish stocks: modelling stock biomass dynamics in multigear fisheries

Abstract: A biomass dynamics modelling study to derive biological reference points and management requirements of 223 commercially important fish stocks in different maritime states of India was conducted. Two decades (1997–2016) of fishery-related data on the harvest of resources by different types of fishing fleets formed the input. The multigear nature of the fishery situation was solved by introducing a gear standardization parameter into the biomass dynamics model. The relative positions of the fish stocks were dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The MLS for this species has been specified based on criteria of size at sexual differentiation into male and female, based on the premise that this species has high reproductive potential and hence biomass are not significantly affected by high fishing pressure (Mohamed et al, 2014). However, a recent study on the analysis of the stock status of this species along the Gujarat waters shows that this species is overfished (Sathianandan et al, 2021), which cautions the need for high conservation status for this species. Hence, as a precautionary measure, it would be better to maintain the MLS same as that of LFM, for this species till the stock status improves.…”
Section: Discussionmentioning
confidence: 99%
“…The MLS for this species has been specified based on criteria of size at sexual differentiation into male and female, based on the premise that this species has high reproductive potential and hence biomass are not significantly affected by high fishing pressure (Mohamed et al, 2014). However, a recent study on the analysis of the stock status of this species along the Gujarat waters shows that this species is overfished (Sathianandan et al, 2021), which cautions the need for high conservation status for this species. Hence, as a precautionary measure, it would be better to maintain the MLS same as that of LFM, for this species till the stock status improves.…”
Section: Discussionmentioning
confidence: 99%
“…Some countries in Southeast Asia have now published assessments of the status of their fisheries, but they typically do not include time series estimates of abundance and fishing pressure, but instead present summaries of current status (e.g. Rohit et al, 2018; Sathianandan et al, 2021). Rohit et al (2018) estimated that the majority of Indian Oil Sardine stocks are below B MSY , with fishing pressure slightly above U MSY .…”
Section: Discussionmentioning
confidence: 99%
“…Rohit et al (2018) estimated that the majority of Indian Oil Sardine stocks are below B MSY , with fishing pressure slightly above U MSY . Sathianandan et al (2021) estimated the status of a large number of small pelagic fishes and estimated that nine are sustainable, 13 are overfished or subject to overfishing and three are recovering. They estimate that 63% of stocks (of all taxa) are below B MSY and 40% are fished harder than U MSY .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average contributions of ribbonfishes and cephalopods to the total trawl landings of Gujarat during the last 5 years (2015-2019) were 18.8% and 12.8%, respectively, against only 6.3% for croakers, indicating significant diversion of trawl effort towards pelagic and column trawling. Sathianandan et al (2021) studied 223 stocks all along the Indian coast and found the north-west coast of India as the most exploited zone, with 54.2% of the assessed stocks being overfished. However, they have not included any species of croaker or entire croaker as a group in their assessment from the NW coast of India.…”
Section: Otolithes Cuvierimentioning
confidence: 99%